Permanent indwelling peritoneal catheters for palliation of refractory ascites in end‐stage liver disease: A systematic review. (17th July 2019) - Macken, Lucia; Hashim, Ahmed; Mason, Louise; Verma, Sumita
Abstract: Background & Aims: The incidence and mortality from end‐stage liver disease is increasing, with a minority eligible for liver transplantation. Ascites is the commonest complication of end‐stage liver disease and large volume paracentesis (LVP) the accepted management strategy where refractory to medical treatment. In malignant ascites, permanent indwelling peritoneal catheters (PIPC) are an established palliative intervention. The aims are to describe available data using permanent indwelling peritoneal catheters in refractory ascites due to end‐stage liver disease. Methods: Using systematic review methodology, databases were searched (MEDLINE, EMBASE, CINAHL [The Cumulative Index to Nursing and Allied Health Literature], Google Scholar and Cochrane Database of Systematic Reviews from inception‐March 2018), for studies combining ascites and palliative care. Inclusion and exclusion criteria were applied to results. Results: Following initial and updated searches, 225 studies were identified for full text review, 18 were eligible for final analysis. The studies displayed heterogeneity in design, reported on different indwelling catheters and were overall of low quality. Only one pilot randomised controlled trial was identified, of PIPC versus LVP, recruiting one patient into each arm. Technical insertion success was 100%, with low rates of non‐infectious complications (<12%), none life threatening. Rates of bacterial peritonitis were not unacceptably high (12.7%), considering this was an end‐stage liver disease population and only a minority utilising long‐term prophylactic antibiotics. Only one study attempted quality‐of‐life assessments; none addressed potential health economic benefits. Conclusions: Despite lack of well‐designed studies, preliminary data suggests low significant complication rates; however safety and efficacy of permanent indwelling peritoneal catheters in end‐stage liver disease remains to be confirmed. Further prospective randomised controlled trials are warranted, potentially translating permanent indwelling peritoneal catheters into improved palliative care in end‐stage liver disease.